2009
DOI: 10.3153/jfscom.2009039
|View full text |Cite
|
Sign up to set email alerts
|

OTOLITH SIZE-TOTAL LENGTH RELATIONSHIP IN SPINY EEL, Mastacembelus mastacembelus (BANKS & SOLANDER, 1794) INHABITING IN KARAKAYA DAM LAKE (MALATYA, TURKEY)

Abstract: In this study, the relationships between total length and sagittal otolith size of a total 187 specimens belonging to the Mastacembelus mastacembelus (Banks & Solander, 1794) fish species inhabiting Karakaya Dam Lake were examined. The otolith lengths and widths were ranged between 1.44-3.82 mm and 0.8-1.71 mm, respectively. However, otolith weights were determined between 0.0003-0.0038 g. There was a stronger and positive linear relationship between the otolith size (length, width and weight) and total length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
3
0
3
Order By: Relevance
“…Otolith size and shape vary among species and individuals (Eroğlu, Şen, 2009), and may be used for morphometric analyzes. Aguilera et al (2013) used otoliths for paleontological identification of fossil fishes, and Tuset et al (2008) A anchova, Pomatomus saltatrix (Linnaeus, 1766), foi usada como modelo espécie-específico de relações morfométricas de otólitos e variáveis de crescimento relativo.…”
Section: Introductionunclassified
“…Otolith size and shape vary among species and individuals (Eroğlu, Şen, 2009), and may be used for morphometric analyzes. Aguilera et al (2013) used otoliths for paleontological identification of fossil fishes, and Tuset et al (2008) A anchova, Pomatomus saltatrix (Linnaeus, 1766), foi usada como modelo espécie-específico de relações morfométricas de otólitos e variáveis de crescimento relativo.…”
Section: Introductionunclassified
“…Otolith biometry-body length relationships have been determined for many fish species by different investigators (Gamboa, 1991;Harvey et al, 2000;Waessle et al, 2003;Longenecker, 2008;Battaglia et al, 2010;Zorica et al, 2010;Potier et al, 2011;Skeljo and Ferri, 2012). In Turkey, although a number of studies have been reported on relationships between otolith size and fish length (Şahin and Güneş, 1998;Can, 2000;Ceyhan and Akyol, 2006;Samsun and Samsun, 2006;Bostancı and Polat, 2008;Eroğlu and Şen, 2009;Bostancı et al, 2009;Bostancı et al, 2012;Cengiz et al, 2012;Basusta et al, 2013;Bilge, 2013;İşmen et al, 2013), such information is still lacking for many members of the ichthyofauna. On the other hand, the studies on otolith features of cyprinid fishes have shown an increase in recent years (Şen et al, 2001;Aydin et al, 2004;Bostancı et al, 2007;Gumus et al, 2007;Bostancı, 2009;Bostancı and Polat, 2011;Kontaş, 2012;Basusta et al, 2013;Keskin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The application of otolith only is not restricted to ichthyology, but also extended widely for some aspects of palaeontology, stratigraphy, archaeology and zoogeography (Tuset et al 2008). The size and shape of otoliths are variable according to species and size of fish (Eroglu & Sen, 2009). The relationship between fish length and otolith dimensions, can be useful to estimate the size and age of prey collected from stomach and feeding habits of fishes (Hunt, 1992;Granadeiro & Silva, 2000;Khodadai & Emadi, 2004, Pombo et al 2005, Rizkalla & Bakhoum, 2009Javor et al 2011).…”
Section: Introductionmentioning
confidence: 99%